Immlunology: A Short Course - Richard Coico (Wiley-Blackwell, 2009)
Immunology: A Short Course, Sixth Edition introduces all the critical topics of modern immunology in clear and succinct yet comprehensive fashion. The authors offer a uniquely balanced coverage of classical and contemporary approaches, basic and clinical aspects. As with the previous editions, the strength of the text is in a complete review of modern immunology without burdening the reader with excessive data or theoretical discussions. Each chapter is divided into short, self-contained units that address key topics illustrated by uniformly drawn, full-color illustrations, many brand new to this edition. The sixth edition of this successful textbook newly covers: Toll-like receptors, their ligands and intracellular activation pathways The key role of activation induced cytidine deaminase (AID) in somatic hypermutation and class switch recombination. The autoimmune regulator (AIRE) gene in self-tolerance and autoimmunity T and B cell activation and the immunological synapse, as well as characterization and mechanisms of action of T regulatory cells